Challenges in Tahfidz Al-Qur’an Learning: A Study of Students at Nurul Fikri Islamic Integrated Elementary School, Bengkulu City - Saepudin Saepudin; Nurlaili Nurlaili; Meri Lestari (GHAITSA : Islamic Education Journal, 2026)
This study aims to analyze the challenges faced in the implementation of Tahfidz Al-Qur’an learning among students at Nurul Fikri Islamic Integrated Elementary School, Bengkulu City. Tahfidz Al-Qur’an learning plays an important role in strengthening students’ religious character and improving their ability to memorize the Qur’an from an early age. However, in practice, various obstacles often emerge that affect the effectiveness of the learning process. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results of the study indicate that several challenges were encountered in the implementation of Tahfidz Al-Qur’an learning, including students’ varying memorization abilities, limited learning time, lack of students’ motivation and concentration, and differences in parental support at home. In addition, teaching strategies and the availability of learning resources also influence the effectiveness of the Tahfidz program. Therefore, teachers need to apply appropriate strategies, provide motivation, and collaborate with parents to support students’ memorization progress. This study contributes to understanding the challenges of Tahfidz learning and provides insights for improving Qur’an memorization programs in Islamic elementary schools.